(untitled) (Research, Society and Development, 2022)
The success of an endodontic surgery depends on the removal of a persistent infection from the external apical surface and necrotic tissue or contaminated filling material within the root canal system followed to a complete filling of the root end preparation. The current concepts of surgical endodontics recommend that its execution with the use of magnification and illumination of the operating microscope, which allows an easier identification of the root apices, small ostectomies and smaller apex resection angles. The objective of this article is to report and discuss a clinical case of endodontic microsurgery where the main resources currently recommended were used to increase the success in surgical endodontics. Based on specific equipments, instruments and materials the endodontic microsurgery increases the predictability of success of the surgery. Among the main advances compared to traditional surgery we could observe less trauma to the operated region which resulted in a faster and more comfortable healing for the patient.